Outsourcing Software Development Offshore: Making It Work - Gold, Tandy (CRC Press, 2009)
In Offshore Software Development: Making It Work, hands-on managers of Offshore solutions help you answer these questions: · What is Offshore and why is it an IT imperative? · What do you need to do to successfully evaluate an Offshore solution? · How do you avoid common pitfalls? · How do you confront security and geopolitical risk? · How do you handle issues related to displaced workers?